Alloying nickel and cobalt with iron on ZSM-5 for tuning competitive hydrogenation reactions for selective one-pot conversion of furfural to gamma-valerolactone. Issue 45 (3rd November 2022) - Shao, Yuewen; Guo, Mingzhu; Fan, Mengjiao; Sun, Kai; Gao, Guoming; Li, Chao; Bkangmo Kontchouo, Félix Mérimé; Zhang, Lijun; Zhang, Shu; Hu, Xun
Abstract : One-pot conversion of furfural to gamma-valerolactone in ethanol was achieved over a bifunctional Ni–Co–Fe/ZSM-5 catalyst with alloy sites and acidic sites. Abstract : One-pot conversion of furfural, a biomass-derived platform chemical, to gamma-valerolactone (GVL), a fuel additive and green solvent, involves multiple steps of hydrogenation. Among these reactions, the deep hydrogenation of the furan ring in furfural interrupts GVL formation over Ni or Co-based catalysts. In this study, a method of alloying Ni and Co with Fe over a ZSM-5 support was proposed for tackling excessive activity of the catalyst for hydrogenation. The results indicated that the formation of binary NiFe and CoFe alloys in Ni–Co–Fe/ZSM-5 enhanced the dispersion of metallic species, reduction of metal oxides, formation of more Lewis acidic sites, and the adsorption of the C–O functionality of the furan ring, while lowering the capability for adsorption/activation of H2 and the adsorption of the CC group of the furan ring. These factors together reduced the activity for the hydrogenation of the furan ring in furfural, but enhanced the hydrogenation of the CO in ethyl levulinate (EL). The kinetic study confirmed that the hydrogenation of EL was the rate-determining step. The coordination of the dual alloys, NiFe and CoFe, in the bifunctional Ni–Co–Fe/ZSM-5 catalyst rendered superior activity for selective one-pot conversion of furfural to GVL with a yield of 85.7%.